A rare case of two superior vena cava with two azygos veins in a cadaver - Archana Singh; Rakesh Gupta; Priya Rani Adhaya; Aleeza Muneer (Wolters Kluwer Medknow Publications, 2023)
In embryonic life developmental malformation of thoracic veins can lead to anomalies of the Superior vena cava and major thoracic veins like Azygos system. Double superior vena cava and double azygos vein are rare congenital anomaly with the incidence of 0.3%. These types of congenital anomalies may or may not be presented with clinical symptoms. This case was noted during the routine cadaveric dissection of thoracic region and heart for medical students in department of Anatomy, we found double superior vena cava (persistent left superior vena cava) along with double (paired) azygos vein in a female cadaver. Right superior vena was formed by the union of right subclavian and right internal jugular vein which receives the arch of right azygos before it opened into the right atrium. Left superior vena cava was formed by the union of left subclavian and left internal jugular vein and it also receives the arch of left azygos vein before it entered into the right atrium. In present case coronary sinus was separated from left persistent superior vena cava and it opened in the persistent left superior vena cava. There was no communication between both the superior vena cava. On right side Azygos vein was normal and open into right superior vena cava. On the left side hemiazygos was in continuation with the accessory azygos vein and it also forming the arch and opened into persistent left superior vena cava. There were no other congenital anomalies present in the heart. These types of congenital anomalies extremely very rare where the left superior vena cava opens into the right atrium directly and coronary sinus opens in to this left superior vena cava. Majority of such types of cases remain asymptomatic. Some cases may be detected accidently during diagnostic or surgical procedures like cardiac angiography, cardiac catheterization, by- pass and dialysis or during autopsy or institutional cadaveric dissection.